2016
DOI: 10.5194/isprsannals-iii-8-19-2016
|View full text |Cite
|
Sign up to set email alerts
|

A Meteorological Risk Assessment Method for Power Lines Based on Gis and Multi-Sensor Integration

Abstract: ABSTRACT:Power lines, exposed in the natural environment, are vulnerable to various kinds of meteorological factors. Traditional research mainly deals with the influence of a single meteorological condition on the power line, which lacks of comprehensive effects evaluation and analysis of the multiple meteorological factors. In this paper, we use multiple meteorological monitoring data obtained by multi-sensors to implement the meteorological risk assessment and early warning of power lines. Firstly, we genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…With GIS, users can better understand patterns, relationships, and the context of geographic information, leading to better communication and enhanced efficiency, management, and decision-making. It is also observed that there is a growing trend in the use of GIS within the electrical sector (ESRI, 2010;Husain et al, 2012;Kakumoto et al, 2016;Kezunovic et al, 2015;Korir & Ngigi, 2015;Leite et al, 2019;Li et al, 2014;Lin & Xu, 2016;Rahman et al, 2020;Yatim et al, 2019;Yan et al, 2016;Zheng et al, 2021).…”
Section: Figure 1 History Of Lightning Location System In Peninsular ...mentioning
confidence: 99%
“…With GIS, users can better understand patterns, relationships, and the context of geographic information, leading to better communication and enhanced efficiency, management, and decision-making. It is also observed that there is a growing trend in the use of GIS within the electrical sector (ESRI, 2010;Husain et al, 2012;Kakumoto et al, 2016;Kezunovic et al, 2015;Korir & Ngigi, 2015;Leite et al, 2019;Li et al, 2014;Lin & Xu, 2016;Rahman et al, 2020;Yatim et al, 2019;Yan et al, 2016;Zheng et al, 2021).…”
Section: Figure 1 History Of Lightning Location System In Peninsular ...mentioning
confidence: 99%
“…(1) Weather conditions: this was divided by region, and the confidence calculation results are shown in Table 2: (2) Altitude: this could be divided into four grades, and the confidence calculation results are shown in Table 3: (3) Topography: this could be divided into three grades, and the confidence calculation results are shown in Table 4: (4) Tower height: this could be divided into four grades, and the confidence calculation results are shown in Table 5: (5) Voltage grade: this could be divided into three grades, and the confidence calculation results are shown in Table 6: (6) Tower model: this could be divided into six grades, and the confidence calculation result is shown in Table 7: The total number of overhead transmission line towers in the data was 15,847, and the number of impact factors was six. The mass function value was calculated using the entropy method and gray correlation analysis, then the modified Mass function value of each influence factor was obtained using Equations ( 8)- (10), and finally, the trust degree function Bel(K i ) of 15,847 towers was calculated according to Equation (11).…”
Section: Calculation Of Lightning Failure Riskmentioning
confidence: 99%
“…In the literature [10], the analytic hierarchy process was improved, and a full level assessment system was established, which could comprehensively analyze various impact factors of lightning risk. In the literature [11], meteorological monitoring data were collected using multi-sensors, and a meteorological risk assessment model was established based on an analytic hierarchy process using expert scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation